Improving the accuracy of determining corrosion products in reinforced concrete structures by atomic emission spectrum analysis - A. A. Kuznetsov; N. V. Volkova; K. I. Fomichenko; D. M. Korshunov (Омский научный вестник)
To determine the composition of inhomogeneous samples using the method of laser-spark emission spectrometry, calibration dependences are used, which can have significant systematic errors that significantly affect the determination of the quantitative composition of elements. Sample inhomogeneity also causes inaccuracies in replicate measurements. To reduce errors, multi-signal calibration and internal standard methods are used, which can significantly improve accuracy when changing experimental conditions and eliminate the need to purchase ex-pensive standard samples.